The Polysemy of Beside: The Correlation between TR and LM Syntactic Elaborations and Meaning - Brenda, Maria (Research in Language, 2024)
The paper contributes to the discussion of the polysemy of spatial prepositions looking at the conceptual structure of the preposition beside. Introducing the syntactic criterion to the process of trajector/landmark identification, the paper shows that beside gives access to a three-dimensional conceptual category, extending both upward and sideways, and that its polysemy arises when the conceptualizer focuses attention on the basic level of the category, the level of senses.